(untitled) (International Journal of Engineering and Computer Science, 2013)
As deployed Grids increase from tens to thousands of nodes, Peer-to-Peer techniques and protocols can be used to implement scalable services and applications. The Address allocation model is a novel approach that helps the convergence of wireless network and Grid environments and can be used to deploy information service in Grids. A Deterministic peer serves a single Virtual Organization (VO) in a Grid, and manages metadata associated to the resources provided by the nodes of that VO. In our proposed research work we need to connect each other to form a peer network at a higher level. This paper examines how the proposed architecture can be used to handle membership management and resource discovery services in a multi-organizational Grid. A simulation analysis evaluates the performance of a resource discovery protocol; simulation results can be used to tune protocol parameters in order to increase search efficiency. As we know that data transmission by the electronic signals are growing very highly so the fault tolerance are making so difficult by performing the proposed address resolution scheme we can get the desired result in wireless area network